A confused ECG with multiple rhythms caused by atrial premature contractions: A case report. Issue 50 (December 2017) - Hongliang, Yang; Ming, Yu; Qini, Zhao; Daoyuan, Si; Yaliang, Tong; Ying, Wang; Yuquan, He
Abstract: Introduction: Atrial premature contractions (APCs) are commonly encountered in clinical practice. The APCs may influence heart conduction system and induce other arrhythmia. The disorder of atrioventricular conduction is related to electrophysiological phenomena, difficult to understand and diagnose. Case report: We presented a 15-year-old male patient whose baseline electrocardiogram (ECG) was confused with multiple rhythms. Electrophysiological study results showed sinus rhythm with nonconducted APCs in bigeminal rhythm. Nonconducted APCs were blocked without H wave. Some APCs conducted to ventricle with longer AH interval and HV interval. When APCs were abolished by radiofrequency ablation, this patient was free from any arrhythmia during follow-up. Conclusion: We considered that the basic rhythm of the baseline ECG was sinus rhythm with atrial bigeminy rhythm and narrow QRS extrasystoles (junctional); some APCs were blocked and some APCs conducted to ventricle with aberrant QRS complexes. The phenomenon of baseline ECG was caused by the APCs.